EPISTEMOLOGI KONSTRUKSIONISME SEBAGAI DASAR PENELITIAN SOSIAL - kamaludin, kamaludin (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2023)
Hadith research is research that has a wide range of objects. In addition to focusing on internal aspects related to the text, such as research on matan and narrators, hadith research also includes matters relating to the content of hadith on the dynamic human life with the struggles of other human implementations. In this case, further hadith research reaches aspects related to social research in general which has an epistemology of the basics of acquiring a distinctive knowledge, one of which is the epistemology of constructionism. This research uses the literature study method which aims to describe how the constructivism epistemology in social research is. The result of this research is that the epistemology of constructionism is a critique or opponent of the positivism paradigm, which is a criticism or opponent of the positivism paradigm which has a transactional relationship pattern (responsible) for the object under study and participatory dialectics (going directly into the reality of society).